Dampak Penurunan Suku Bunga Kredit terhadap Penyaluran Kredit di LPD Kuta Saat Pandemi Covid-19 - Ni Made Devi Pratiwi; I Gst Ayu Wirati Adriati (UNHI Press, 2020)
LPD is one of the institutional elements of Customary Villages that carry out the functions of customary village finance to manage village financial potential. The purpose of the activities carried out are to determine the impact of lowering lending rates on lending, knowing the causes of lowering lending rates on lending, and knowing the solutions used to overcome the impact of reducing lending rates on lending. The method used in this street vendor activity is in the form of a review method where the review begins with the stage of searching for the title and location, searching for data, and conducting an analysis to find out how the impact of lowering lending rates on lending. The results obtained from the implementation of this activity are the impact of a decrease in lending rates on lending that is decreasing lending in Kuta LPD, the cause is due to the absence of the public or customers who do credit during Pandemic Covid-19 or in other words the demand declining credit, and delaying interest payments and socializing the importance of saving into a solution that must be done.